Imprisoned comicality: the performativity of aesthetic experiences in anti-racist education revealed for the teaching of theater - Franco, Elison Oliveira (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2026)
This text aims to intertwine the production of knowledge arising from aesthetic experiences in the performing arts, through the body in performances of spiral time (Martins, 2021) and their archives (Rabetti, 2000), with the promotion of anti-racist education in basic education. It analyzes the phenomenology of the comic and learning processes from various social and cultural contexts that seek to combat racism. To this end, the study presents an empirical, reflective, and theoretical account by the author-teacher concerning his practices and forms of knowledge within the universe of the performing arts, focusing on the comicality, laughter, and the figure of the clown. This discussion aligns with contents related to the teaching and learning process of theater in public schools, with particular attention to Law No. 10,639/2003, which mandates the teaching of Afro-Brazilian history and culture in the classroom (Brasil, 2003).